2012
DOI: 10.2147/ijn.s32476
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, characterization, and evaluation of in vitro skin permeation and in vivo pharmacodynamics of surface-charged tripterine-loaded nanostructured lipid carriers

Abstract: Background: Nanostructured lipid carriers (NLCs) are attractive materials for topical drug delivery, and in a previous study, we demonstrated that NLCs loaded with tripterine enhance its deposition. However, the surface charge of nanoparticles influences percutaneous drug penetration. Therefore, we aimed to evaluate the influence of the surface charge of NLCs on in vitro skin permeation and in vivo pharmacodynamics of tripterine and optimize tripterine-loaded NLCs for the treatment of skin diseases. Methods: D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Nevertheless, all formulations displayed adequate sizes between 100 and 200 nm. Due to the dissociation of protons from the carboxylic groups of Precirol after dilution in deionized water (pH 5.6), NLCs exerted a negative superficial charge, which was found to be around −20 mV for all nanoformulations and thus all of them might have good physical stability [55,56]. In contrast, olive oil content significantly affected the freeze-drying process of the NLCs.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, all formulations displayed adequate sizes between 100 and 200 nm. Due to the dissociation of protons from the carboxylic groups of Precirol after dilution in deionized water (pH 5.6), NLCs exerted a negative superficial charge, which was found to be around −20 mV for all nanoformulations and thus all of them might have good physical stability [55,56]. In contrast, olive oil content significantly affected the freeze-drying process of the NLCs.…”
Section: Resultsmentioning
confidence: 99%
“…The permeability coefficient (Kp, measured in cm/h) was calculated from the following equation: where Cd represents the drug concentration applied on the skin in the donor compartment. 28 …”
Section: Methodsmentioning
confidence: 99%
“…In the present study, NLCs and LPNs showed a mean size of about 100 nm. NLCs are reported to have the abilities of biocompatibility, modified release kinetics which are suitable for topical drug delivery (Chen et al., 2012 ). LPNs are argued to have controlled release capability, high biocompatibility, and favorable pharmacokinetic profile, while may have an influence on the drug transdermal permeation (Zhang et al., 2015 ; Liu et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%